Formality, Agility, Security, and Evolution in Software Development. - Bowen, Jonathan P.; Hinchey, Mike; Janicke, Helge; Ward, Martin; Zedan, Hussein (Computer (00189162), 2014)
Combining formal and agile techniques in software development has the potential to minimize change-related problems.